1982
DOI: 10.1159/000194497
|View full text |Cite
|
Sign up to set email alerts
|

Nebulised Sodium Cromoglycate in the Treatment of Wheezy Bronchitis in Infants and Young Children

Abstract: 44 children under 2 years of age suffering from recurrent or persistent wheezy bronchitis, completed a double-blind crossover trial comparing nebulised sodium cromoglycate and matching placebo. Analysis showed that treatment response was age-related. Sodium cromoglycate proved significantly superior to placebo in reducing night cough, sleep disturbance, wheeze and activity limitation in the 24 patients aged 12 months and above (mean 17.3) on entry to the study. Whereas no significant differences were observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 6 publications
(6 reference statements)
2
17
0
Order By: Relevance
“…We could not identify subgroups of children whose response to cromoglycate was influenced by age, sex, positive family history, atopic history, season, or smoking habits of the parents. GellerBernstein and Levin 11 found an effect of cromoglycate in children aged 12 months and older, whereas no effect was seen in children below this age.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…We could not identify subgroups of children whose response to cromoglycate was influenced by age, sex, positive family history, atopic history, season, or smoking habits of the parents. GellerBernstein and Levin 11 found an effect of cromoglycate in children aged 12 months and older, whereas no effect was seen in children below this age.…”
Section: Discussionmentioning
confidence: 97%
“…6,7 Despite widespread use, the effect of inhaled sodium cromoglycate in very young children with moderate asthma has hardly been studied. Several placebocontrolled trials [8][9][10][11][12][13][14][15][16][17][18] have been reported but most were hospital-based, studied patients with severe asthma, had follow-up periods shorter than 10 weeks, and studied medication inhaled by nebulisation. Six of these studies showed improvement of symptoms in comparison with placebo, [8][9][10][11][12][13] but in five sodium cromoglycate was no better than placebo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 In most infants with GER and wheezing, appropriate medical management improves GER and respiratory symptoms secondary to GER. 1,9,10 Management of infants with daily wheezing is difficult, and the role of asthma medications such as oral theophylline 11 and nebulized sodium cromoglycate 12,13 is controversial. This may be because infantile wheezing is a common presentation with many different etiologies, such as exposure to smoking, GER, upper respiratory viral infections, or asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium cromoglycate (SCG) is a useful prophylactic agent in symptomatic children less than 5 years of age [1,4,6]. In a randomised controlled trial [13] …”
Section: Introductionmentioning
confidence: 99%